2015
DOI: 10.1007/s10883-015-9308-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic Chain Control Sets on Flag Manifolds

Abstract: In this paper, we characterize the hyperbolic chain control sets of a right-invariant control system on a flag manifold of a real semisimple Lie group. Moreover, we provide a formula for the invariance entropy of such sets, applying a recently established result that holds in a more general setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Section 7 is devoted to the application of the above characterization to the estimation of the invariance entropy of invariant systems on flag manifolds from below. It is shown that if the Morse spectrum associated with the center bundle is trivial, then the infimum, on the associated Morse set, of the exponential growth rate of the unstable determinant is a lower bound for the invariance entropy, generalizing the previous result in [11] proved for the case of a vanishing center bundle. Some concepts and technical lemmas that are used in the main results are stated in an appendix, Section A.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Section 7 is devoted to the application of the above characterization to the estimation of the invariance entropy of invariant systems on flag manifolds from below. It is shown that if the Morse spectrum associated with the center bundle is trivial, then the infimum, on the associated Morse set, of the exponential growth rate of the unstable determinant is a lower bound for the invariance entropy, generalizing the previous result in [11] proved for the case of a vanishing center bundle. Some concepts and technical lemmas that are used in the main results are stated in an appendix, Section A.…”
Section: Introductionsupporting
confidence: 60%
“…In this case, Θ(φ) = ∅ and by [11,Thm. 4.6] any chain control set E Θ (w) of the induced system Σ Θ on F Θ is uniformly hyperbolic without center bundle for any choice of Θ, i.e., E 0 Θ,w is trivial.…”
Section: Figure 1: Morse Spectramentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, we introduce the following notion of hyperbolicity for controlled invariant sets of (1). A class of examples satisfying this definition is characterized in [4].…”
Section: The Entropy Formula For Hyperbolic Chain Control Setsmentioning
confidence: 99%